2017
DOI: 10.1016/j.antiviral.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for serum chemokine/cytokine assessment as biomarkers of therapeutic response in HCV patients as a prototype to monitor immunotherapy of infectious diseases

Abstract: In this study, strategies for serum biomarker assessment were developed for therapeutic monitoring of HCV patients. For this purpose, serum chemokine/cytokine levels were measured by cytometric-bead-array in HCV patients, categorized according to immunotherapy response as: non-responder/NR, relapser/REL and sustained-virologic-responder/SVR. The results demonstrated an overall increase of serum chemokine/cytokine levels in HCV patients. In general, therapeutic failure was associated with presence of a predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In this study, IL-6 levels were not significantly altered after antiviral therapy. Confirming our results, IL-6 serum levels were not altered after DAA treatment in another Brazilian cohort with chronic hepatitis C patients [ 20 ]. Interestingly, another Brazilian study suggests that IL-6 and TNF polymorphisms might lead to a distinct range of proinflammatory cytokines [ 23 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, IL-6 levels were not significantly altered after antiviral therapy. Confirming our results, IL-6 serum levels were not altered after DAA treatment in another Brazilian cohort with chronic hepatitis C patients [ 20 ]. Interestingly, another Brazilian study suggests that IL-6 and TNF polymorphisms might lead to a distinct range of proinflammatory cytokines [ 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the occurrence of downregulation of inflammatory and fibrotic biomarkers in association with HCV eradication after antiviral therapy is still unclear. Some authors demonstrated an increase in inflammatory mediators' serum levels after the end of IFN-based treatment [ 16 20 ]. Other studies reported decreased inflammatory biomarkers in plasma of chronic hepatitis C patients after IFN-free regimens including the newer DAA, although normalization was not reached [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study also confirms that the production of inflammatory cytokines and chemokines is enhanced in patients with chronic HCV infection and is downregulated by viral eradication . Indeed, antiviral therapy significantly improved IL1‐ra, IL2, IL5, FGF‐basic, GM‐CSF, IFN‐gamma, CCL2, CCL3, CCL4, CCL11, CXCL10, PDGF‐BB, and TNF‐alpha plasma levels.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, this result may be affected by the relatively short follow-up period, as the evaluation of these parameters was performed 1 year after the end of the DAA treatment, and also by the fact that only patients with well-compen- Our study also confirms that the production of inflammatory cytokines and chemokines is enhanced in patients with chronic HCV infection and is downregulated by viral eradication. [28][29][30][31][32][33][34][35][36][37] Indeed, antiviral therapy significantly improved IL1-ra, IL2, IL5, FGF-basic, , faecal calprotectin) before and 1 y after the end of direct-acting antiviral (DAA) treatment. IL: interleukin; ra:receptor agonist; FGF: fibroblast growth factor; G-CSF: granulocyte colony-stimulating factor; GM-CSF: granulocytemacrophage colony-stimulating factor; IFN: interferon; CCL: C-C motif chemokine ligand; CXCL: C-X-C motif chemokine ligand; PDGF: plateletderived growth factor; TNF: tumour necrosis factor GM-CSF, IFN-gamma, CCL2, CCL3, CCL4, CCL11, CXCL10, PDGF-BB, and TNF-alpha plasma levels.…”
Section: P-value (Hcv Post-daa Vs Controls)mentioning
confidence: 99%
“…The study of Fathy et al described a normalizing immune response during treatment concerning IL-17A, in both responders and non-responders, but in a very small number of patients and over a short period of time [ 31 ], while Sousa et al described a non-significant downregulation in their non-responder group. Menezes et al reported that patients with SVR displayed lower IL-17 levels compared with non-responders [ 32 ].…”
Section: Discussionmentioning
confidence: 99%